HUBUNGAN PERSEPSI MAHASISWA TENTANG KOMPETENSI DOSEN, MOTIVASI, MINAT BELAJAR DENGAN HASIL BELAJAR MAHASISWA - Sri Yunita Suraida Salat (Fakultas Ilmu Kesehatan, 2014)
Background:The main problem facingthe worldtodayis the loweducationalachievementof students. Perceptionis one of thepsychological factorsthat influencelearning achievement. Besidesmotivationandinterestis also a factorinlearning achievement.Research methods:design ofthe study iscorrelationalanalyticcross-sectional design. Respondentsin this studyis thethirdsemester studentsProdiDIIIMidwiferyUniversityWirarajayears2012-2013as many as66students. Data collection toolssuch asquestionnaires. Analysis ofdata usingmultiple linearregression test.Results: Theresultsin this studythatthere is a relationshipbetweenstudents' perceptionsofteachercompetencewiththe learning outcomeswithT valuegreater thanttable(2.932>2.353). There is a relationshipbetween motivation andlearning outcomeswithprobabilityvalueindicatesthe valueis smallerthanthe expectedvalue ofα(0.028 <0,05). there isinterest intherelationshipbetweenlearning outcomeswithprobabilityvalueindicatesthe valueis smallerthanthe expectedvalue ofα(0,014 <0,05). ThereRelationsStudentPerceptionsofCompetenceLecturer, MotivationandInterest inLearningwithStudent Learning OutcomesProdiDiplomainMidwiferyUniversityWirarajaSumenepwithprobabilityvalueindicatesthe valueis smallerthanthe expectedvalue ofα(0.000 <0.05).Conclusion:There is arelationshipofCompetenceLecturersStudentPerceptions, MotivationsandInterestsLearningwithStudent Learning OutcomesinDIIIProdiMidwiferyUniversityWirarajaSumenep. Keywords:Perception, Motivation, Interest andLearning Outcomes